Evaluasi Usability Sistem Informasi Audit Internal Mutu pada Pusat Jaminan Mutu Universitas Brawijaya - Rian Rizki Prayogo; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
SIAIM is an application used by the Quality Assurance Center to improve their performance. For several months using SIAIM, users provide feedback on the use of SIAIM applications. User issues gleaned from feedback are about non-functioning